The Relationship of Hand Washing Behavior with Soap and the Incidence of Typhoid Fever in Children Aged 5 - 12 Years in RW 01 Cikembar Village Cikembar District Sukabumi Dist - Marselina, Shella; Ardayani, Tri; Sitorus, Neti (CV Media Inti Teknologi, 2024)
The general aim of this research is to determine the relationship between hand washing behavior with soap and the incidence of typhoid fever in children aged 5-12 years. This research is a quantitative research with a cross sectional approach. The research population was children aged 5-12 years in rw 01, Cikembar village, Cikembar sub-district, Sukabumi district, from August to September 2023, data were obtained for 98 people. The research sample was 98 children aged 5-12 years who were determined using total sampling techniques. Research data was collected using a questionnaire which was then analyzed using chi square analysis. The results of the study showed that the chi square test results of the relationship between hand washing behavior with soap and the incidence of typhoid fever obtained a value (p-Value = 0.000) so that H0 was rejected and the chi square test results of the relationship between snack consumption and the incidence of typhoid obtained a value (p-Value = 0.377) so that H0 is rejected. It is proven that the habit of washing hands before eating influences the incidence of typhoid fever.